'We don't get money in our own hands': evidence from focus group discussions on economic abuse against women in two states of India - Steinert, Janina; Böhret, Ines; Vasumati Satish, Rucha; Sharma, Sanchita; Chatterji, Sangeeta (BMJ global health, 2023)
INTRODUCTION: Violence against women is a serious human rights violation. While much attention has been given to the prevalence and prevention of physical, sexual and emotional violence, one crucial dimension is to date less well understood: economic abuse against women. This paper presents rich qualitative data on economic abuse against women in India to improve the understanding of economic abuse in a lower-middle income setting and to assess how economic abuse interacts with socio-cultural factors such as patrilocality, patriarchal gender norms and limited acceptance of female employment. - METHODS: We conducted 13 focus group discussions (FGDs) in the states Maharashtra and Rajasthan. FGDs were conducted with married working (for income) and non-working women, husbands and mothers-in-law. Discussions were recorded, transcribed verbatim and translated to English. Transcripts were coded using thematic analysis and emerging themes were discussed among all authors. - RESULTS: Women suffered from four distinct forms of economic abuse. Economic control emerged as the most prevalent theme, amplified by women's marginalisation from financial decision-making in the household. Discussions further alluded to employment sabotage, which husbands commonly justified by not wanting their wives to neglect their duties at home. A third category was women's economic exploitation, expressed by husbands taking their salaries, accumulating debt in their wife's name, and using their wife's wedding endowments for own purposes. A last category was husbands' refusal to financially contribute to necessary household expenses, which hindered investments in children's education and adequate coping with health emergencies. We identified important linkages with other forms of domestic abuse. - CONCLUSION: Economic abuse has the potential to trap women in abusive relationships. Effective interventions to reduce economic abuse and economically empower women such as financial inclusion programmes are urgently needed. Stricter penalisation of dowry-related violence and spousal abuse is also required.
Gesehen am 01.08.2024